Cutaneous silent period in ulnar neuropathy at the elbow. Issue 2 (16th November 2021) - Mondelli, Mauro; Aretini, Alessandro
Abstract: Introduction/Aims: The cutaneous silent period (CSP) reflects the function of A‐delta sensory fibers. There are few studies on CSP in nerve entrapment syndromes. This study aims to evaluate the neurophysiological abnormalities of small‐diameter sensory fibers in ulnar neuropathy at the elbow (UNE) by means of CSP. Methods: We consecutively evaluated UNE patients at one electrodiagnostic laboratory. The CSP was obtained upon stimulating the fifth (D5) and third digits, recording from the first dorsal interosseous (FDI) and abductor pollicis brevis (APB) muscles. Results: We enrolled 37 UNE patients (mean age 55.4 ± 11.2 y) and 30 controls (mean age 51.2 ± 11.1 y). The combinations of the D5‐APB and D5‐FDI mean onset latencies of CSP were significantly more prolonged in patients (83.7 ± 6.8 and 84.5 ± 8 ms, respectively) than in controls (78.2 ± 8.1 and 79.4 ± 7.6 ms, respectively). The D5‐FDI duration of CSP was shorter in patients (52.2 ± 8.3 ms) than in controls (55.8 ± 7 ms). The mean of the onset latencies of D5‐FDI and D5‐APB was related to the clinical severity ( P = .013 and .0025, respectively). D5‐APB and D5‐FDI onset latencies were more prolonged and the duration was shorter in the UNE group with absent ulnar sensory nerve action potentials (SNAPs) and axonal motor damage than in patients with preserved SNAPs and with demyelinating damage. Discussion: CSP was able to demonstrate abnormalities of small‐diameter myelinated sensory fibers. This damage was directly related to UNE severity and to axonal damage of motor fibers. Absence of a sensory large‐diameter fiber response did not exclude preserved residual small fiber conduction.